2010
DOI: 10.1038/hr.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in metabolic syndrome prevalence

Abstract: Accumulating evidence has shown that seasonal variations can exist within metabolic syndrome parameters. The aim of this study was to examine the hypothesis that there are seasonal variations in the prevalence of metabolic syndrome in Japanese subjects. We investigated a total of 1202 male workers in our institution (44 ± 10 years) who underwent health checkups in both June (summer) and December (winter) 2008. In this study, metabolic syndrome was defined according to the criteria proposed by the National Chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 20 publications
4
44
0
1
Order By: Relevance
“…potentiating insulin resistance). Moreover, it must be appreciated that this seasonal mechanism for regulating metabolism that has been preserved over hundreds of millions of years of evolution is also manifested in man, as multiple studies have clearly demonstrated [66][67][68][69][70][71][72][73][74][75].…”
Section: Role Of the Biological Clock (Scn) And Circadian Rhythms In mentioning
confidence: 99%
“…potentiating insulin resistance). Moreover, it must be appreciated that this seasonal mechanism for regulating metabolism that has been preserved over hundreds of millions of years of evolution is also manifested in man, as multiple studies have clearly demonstrated [66][67][68][69][70][71][72][73][74][75].…”
Section: Role Of the Biological Clock (Scn) And Circadian Rhythms In mentioning
confidence: 99%
“…Thus, it appears that the seasonal effect has a clear impact. In this issue of Hypertension Research, Kamezaki et al 7 show that serum levels of high-density lipoprotein cholesterol, fasting glucose and systolic and diastolic blood pressures are higher in winter than in summer. Furthermore, these seasonal fluctuations influence the assessment and prevalence of the metabolic syndrome.…”
Section: Isruption Of Endogenous Rhythms Hasmentioning
confidence: 98%
“…[10], исследовав 1202 японских мужчины среднего возраста (44±10 лет), показали вы-сокую распространенность метаболического синдро-ма в зимний период года. По критериям Национальной образовательной программы по холестеролу (National Cholesterol Education Program Adult Treatment), Между-народной федерации диабета (IDF), японского обще-ства внутренней медицины (Japanese Society of Internal Medicine) распространенность зимой метаболического синдрома составила 3,8%; 15,1% и 12,4%, а летом -3,2%; 10,7% и 8,4% соответственно.…”
Section: биологические неклассические эффекты витамина Dunclassified